2014
DOI: 10.1186/1472-6882-14-61
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism studies of erythraline, the major spiroalkaloid from Erythrina verna

Abstract: BackgroundErythrina verna, popularly known as “mulungu”, is a Brazilian medicinal plant used to treat anxiety. Erythrina alkaloids have been described in several species of Erythrina, which have biological and therapeutic properties well known that include anxiolytic and sedative effects.MethodsIn this work, in vitro metabolism of erythraline (1), the major spirocyclic alkaloid of Erythrina verna, was studied in the pig cecum model and by biomimetic phase I reactions. The biomimetic reactions were performed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…Our research group has defined the structure of a putative erythraline metabolite (Fig. , 2b ) in biomimetic procedures; we have also suggested a possible phase I metabolite . In vitro assays have shown that these two compounds do not exert any cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has defined the structure of a putative erythraline metabolite (Fig. , 2b ) in biomimetic procedures; we have also suggested a possible phase I metabolite . In vitro assays have shown that these two compounds do not exert any cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2b) in biomimetic procedures; we have also suggested a possible phase I metabolite. [13] In vitro assays have shown that these two compounds do not exert any cytotoxic effects. Erythraline (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Erythrina Mart. (Leguminoseae-Fabaceae) comprises around 115-118 known species [5][6][7] that grow in tropicalsubtropical regions and in some temperate regions of the world in different ecosystems [7][8][9]. This alkaloid was first isolated from seeds of Erythrina hypaphorus Boerl [10].…”
Section: Commentmentioning
confidence: 99%
“…The alkaloid erythraline ( 40 ), from E. verna barks, had its metabolism evaluated using a biomimetic phase I reaction. The metabolic product was identified as 8‐oxo‐erythraline (Guaratini et al, ). Additionally, the CYP450‐mediated metabolism of erythraline ( 40 ) was assayed using rat and human liver microsomes to predict the in vivo metabolism, affording also 8‐oxo‐erythraline ( 37 ; Marques et al, ).…”
Section: Preclinical Studiesmentioning
confidence: 99%